2014
DOI: 10.1186/1472-6963-14-381
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis in Germany: data analysis of administrative prevalence and healthcare delivery in the statutory health system

Abstract: BackgroundHealthcare-utilization data for multiple sclerosis (MS) are scarce in Germany. The Purpose of the study was to analyse administrative prevalence of MS, medication use and type of specialists involved in MS treatment in the outpatient setting in Bavaria.MethodsPseudonymized claims data from Bavarian Statutory Health Insurance (SHI)-accredited physicians were used. Administrative prevalence of MS was defined as having ≥1 MS diagnosis (International Classification of Diseases, 10th edition, code G35) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
12

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 14 publications
4
35
0
12
Order By: Relevance
“…6,7 This could be due to a bias in our sample, and also to a possibly more widespread usage in recent years, with a larger number of DMTs to choose from. An indication of this might be that 45% of patients were on DMTs that were licensed within the past 10 years (second-generation treatment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 This could be due to a bias in our sample, and also to a possibly more widespread usage in recent years, with a larger number of DMTs to choose from. An indication of this might be that 45% of patients were on DMTs that were licensed within the past 10 years (second-generation treatment).…”
Section: Discussionmentioning
confidence: 99%
“…Petersen et al 6 found that nearly 200,000 people insured in the statutory health insurance had a diagnosis of MS in 2010, while an analysis of administrative claims data in Bayern found that prevalence had increased from 0.123% to 0.175% between 2005 and 2009. 7 With diagnosis already possible after a clinically isolated event, 3 one must also expect a different distribution of the type of MS and the severity of the disease compared to a decade ago: a larger proportion of patients with relapsing-remitting disease and thus of patients in the early stages of the disease with less disability.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 5 years, a large number of studies have come out of Germany (about 2063 studies). Despite this, health care utilization data and analyses for MS are still scarce (45). Some studies (46) were related to the effects of new treatments such as alemtuzumab on safety, effectiveness, and HRQoL.…”
Section: % Of Patientsmentioning
confidence: 99%
“…Die Inanspruchnahme von Arzneimitteln für die verlaufsmodifizierende Therapie wird im Bereich zwischen 41,5 % bis 71,0 % der beobachteten Patienten mit MS beziffert (Flachenecker et al 2008;Hapfelmeier et al 2013;Höer et al 2014). Diese Angaben beziehen sich auf Patienten ungeachtet der Verlaufsform oder der Krankheitsaktivität, sodass die Unterschiede unter anderem auch durch ein unterschiedliches Patientenkollektiv zu erklären sind.…”
Section: Allgemeine Inanspruchnahmeunclassified